Optimization of MSME Digitalization in Badung Regency - Rumiati, I G. A. Ngurah Lita; Utami, Ni Made Satya; Anggarari, Aniceta Ardyahayu; Tripayana, Satya; Yasa, I Gd. Sudi Pertama (Bali Membangun Bali: Jurnal Bappeda Litbang, 2025)
Purpose: Micro, Small and Medium Enterprises (MSMEs) are an important pillar of the Indonesian economy, including in Badung Regency, contributing 61% to GDP and 97% of employment. However, the adoption of digital technology by MSME is still low due to limited digital literacy, infrastructure, and human resources. This study aims to analyze the implementation of MSME digitalization in Badung Regency and formulate effective digital marketing strategies to increase sales. Research Methods: The study used a quantitative descriptive method with secondary data from a survey of MSME digitalization in 6 sub-districts in Badung Regency. The sample consisted of 180 MSMEs selected randomly, with a focus on micro-enterprises. Findings: As many as 70% of MSMEs have implemented digitalization, especially in the fields of financial administration (77%) and marketing (75%). Instagram (48%) and websites (36%) are the most popular marketing platforms. The positive impacts of digitalization include increased turnover (70%) and market expansion (62%), but challenges such as low digital literacy (66%) and poor internet quality (37%) still hinder. Implications: Digitalization has the potential to improve MSME performance, but requires holistic support. Priority programs include providing non-HR intensive application platforms, improving internet quality, and digital literacy training and MSME management.